The impact of SARS-CoV-2 measures on patient samples and complication rates in spine surgery – A single center analysis - Jankovic, Dragan; Krenzlin, Harald; Keric, Naureen; Ottenhausen, Malte (Frontiers in Surgery, 2023)
Objective: Over the past two years during the pandemic, the German health system has taken drastic measures, like the continuous use of face masks for all staff, restrictions of hospital visits as well as cancellation of elective surgical procedures. As a potential side effect of these measures, a significant reduction of surgical site infections was reported for neurosurgical patients. The purpose of our study was to analyze the impact of these measures on spinal surgery. Methods: We performed a retrospective analysis to compare patient samples, procedures and infection rates before (January 2019 – March 2020) and during (April 2020 – June 2021) the pandemic to evaluate the impact of the measures mentioned above. Demographic and clinical data were collected and correlated with the occurrence of postoperative complications, especially infection. Results: Our analysis showed no relevant decrease of spine surgeries (838 surgeries in non-pandemic group vs. 831 surgeries pandemic group). The most common postoperative complication was wound infection in both groups, followed by urinary tract infection and pneumonia. In both patient groups, infections were more prevalent in surgeries of multilevel posterior instrumentation. Comparing the two groups of patients, a slight, non-significant (0.5 %) reduction of overall postoperative complications in the pandemic group was observed. However, the number of spinal surgeries classified as emergencies in our institution increased by 10.2 % during the last 15 months of the COVID-19 pandemic. In line with this finding the urgent transfer of patients from smaller hospitals increased by 17 %, compared to previous years. Conclusion: The volume of spinal surgeries remained high and complication rates stable during the pandemic. A reason why complication rates did not drop as reported previously might be a significant change in patient sample due to the increase of emergency surgeries. A decrease of complication rates, especially infections by the measures of infection prevention for the pandemic was not observed.